Risk of thrombosis and mortality in inflammatory bowel disease - Andrade, Adriana R. (Clin Transl Gastroenterol, 2018)
OBJECTIVES: Patients with inflammatory bowel disease have a higher risk of thrombosis, which is associated with a higher morbidity and mortality. Most data about VTE are related to hospitalized patients with active disease, but several cases happen in the outpatient setting, and are not covered by current prophylaxis recommendation. As the knowledge of VTE in outpatients is still poor, the aim of this study is to evaluate the risk, clinical data and mortality of thrombosis in patients followed in our center, comparing our findings with the current prophylaxis recommendation. METHODS: The medical electronic chart of 1093 inflammatory bowel disease patients and their image exams were actively searched for words related to thrombosis, followed by charts reviewed to collect information about the event and data regarding clinical settings and thrombosis profile. RESULTS: Overall, 654 Crohn’s and 439 Colitis patients were included. Thrombosis prevalence was 5.1%,and mortality rate was higher in patients who had suffered thrombosis (10.71% vs. 1.45%, OR 8.0). Half of them developed thrombosis in the outpatient setting, 52% of these had disease activity, 17% had recent hospitalization, and 10% had previous thrombosis. In 27% of cases, diagnosis was done by routine image exams, with no clinical symptoms or previous history of thrombosis. None of them had used thromboprophylaxis. However, a great majority of patients who had thrombosis during hospitalization used heparin prophylaxis. CONCLUSION: Inflammatory bowel disease patients who develop thrombosis have an increased mortality risk. A significant proportion of the events happened in patients without a clear thromboprophylaxis recommendation or in those receiving heparin prophylaxis.